The Changing Epidemiology of β-Thalassemia in the Greek-Cypriot Population. (October 2013) - Kyrri, Andreani R.; Kalogerou, Eleni; Loizidou, Dena; Ioannou, Christina; Makariou, Christina; Kythreotis, Loukas; Phylactides, Marios; Kountouris, Petros; Angastiniotis, Michael; Modell, Bernadette; Kleanthous, Marina
<x xml:space="preserve">Abstract</x> The first epidemiological study for thalassemia in Cyprus was performed by Fawdry in 1946. The study determined that the frequency of β-thalassemia (β-thal) carriers was around 18.0% and that of α0-thal carriers (individuals with both cis α-globin genes inactive) at around 2.0%. In 1998, another study concluded that Cyprus had one of the highest frequencies of β-thal carriers worldwide (17.2%). Based on Haldane's hypothesis that malaria might be the selective agent responsible for the maintenance of high levels of thalassemia and sickle cell disease in many populations around the world, it is expected that following the eradication of the disease in Cyprus in 1948, the carriers of β-thal should decline with each generation. In order to determine whether this has been the case, we compiled frequency data for β-thal carriers from three separate surveys performed as part of the Cyprus National Thalassaemia Screening Programme (NTSP). The surveys were carried out in 1986, 2003 and 2010 involving 9622, 6711 and 5228 subjects, respectively. The expected drop in the prevalence of β-thal carriers for each successive generation following the eradication of malaria, i.e., in the absence of selection pressure, was calculated using the Hardy-Weinberg equation and the mathematical model of Hartl and Clark. The surveys provide supporting evidence for the decrease of the frequency of the β-thal carriers in the Greek Cypriot population, with a drop of 1.89% in 24 years.